Evaluasi penerapan sistem dan prosedur uang persediaan pada biro pengadaan barang dan jasa Provinsi Sulawesi Utara - Rengkung, Christina Natalia Gracia; Sabijono, Harijanto; Mawikere, Lidia M. (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to evaluate the implementation of the cash advance system and procedures at the North Sulawesi Provincial Goods and Services Procurement Bureau based on Minister of Home Affairs Regulation No. 77 of 2020 using a descriptive qualitative method through interviews and documentation. The results of the study indicate that the cash advance system and procedures have been implemented properly and in accordance with Permendagri No. 77 of 2020, even though the PBJ Bureau only received a cash advance transfer from the North Sulawesi Provincial Secretariat amounting to Rp. 50,000,000. All procedures, from the issuance of SPP-UP, SPM-UP, SP2D, to accountability reports, have been carried out in accordance with the provisions using the imprest method and the Regional Government Information System (SIPD), which facilitates the documentation and reporting process. The study concluded that the implementation of the cash advance system and procedures at the PBJ Bureau has met the standards of accountability and transparency in regional financial management in accordance with applicable regulations.